PENGARUH JENIS DAN KONSENTRASI ZAT PENGATUR TUMBUH PADA INDUKSI KALUS EMBRIOGENIK KLON CENDANA (Santalum album Linn.) - Toni Herawan; Mohammad Na'iem; Sapto Indrioko; Ari Indrianto; Liliek Haryjanto; Titis Budi Widowati (Jurnal Pemuliaan Tanaman Hutan, 2017)
Sandalwood (Santalum album Linn.) is a tree which has a high rate of natural sprouting ability. Eventhough the propagation by the conventional techniques (shoot and root cuttings) and by the tissue culture have been reported, the percentage of plants regeneration is still low. The propagation using somatic embryogenesis was reported as better result than using shoots multiplication technique or organogenesis. The objective of this research is to examine the effect of clones, type and concentration of plant growth regulator on the development embryogenic callus of sandalwood. The three tested clones are C1, C2, and C3. The plant growth regulators are 2.4-D, Dicamba, and Picloram with the three level of concentrations:1 mg/L, 3 mg/L, and 5 mg/L. The result of study showed that the clone of C3 performed best on embryogenic callus development. It was observed through morphological analysis that 58.12% of explants performed embryogenic callus with friable texture and white, yellowish in colours. However, there were not significant differences between the types of plant growth regulator, the level of concentrations and their interactions on embryogenic callus development of sandalwood